2010
DOI: 10.1007/s00125-009-1644-9
|View full text |Cite
|
Sign up to set email alerts
|

Four-year metabolic outcome of a randomised controlled CD3-antibody trial in recent-onset type 1 diabetic patients depends on their age and baseline residual beta cell mass

Abstract: Aims/hypothesis The aim of the study was to examine the 48 month outcome of treating recent-onset type 1 diabetic patients for 6 days with humanised CD3-antibody, ChAglyCD3. Methods Eighty patients, aged 12-39 years, were recruited for a phase 2 multicentre trial and randomised to placebo (n=40) or ChAglyCD3 (n=40) treatment by a third party member; participants and care-givers were blinded. The change in insulin dose (U kg −1 day −1 ) over 48 months was chosen as primary endpoint and compared in 31 placeboand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
242
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(255 citation statements)
references
References 33 publications
8
242
0
5
Order By: Relevance
“…Treatment with anti-CD3 is a promising avenue of therapy for T1D. When administered early after disease onset, it has been shown repeatedly to reverse diabetes in NOD mice and preserve residual β-cell function in T1D patients for 12-24 mo (35)(36)(37)(38). Although most diabetic NOD mice treated with anti-CD3 revert to normoglycemia, the treatment does not permanently abolish the autoimmune lesion in the pancreas; rather, a stable state of insulitis is established, with a demarcation between the inflammatory infiltrate and β-cell mass (39, 40) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with anti-CD3 is a promising avenue of therapy for T1D. When administered early after disease onset, it has been shown repeatedly to reverse diabetes in NOD mice and preserve residual β-cell function in T1D patients for 12-24 mo (35)(36)(37)(38). Although most diabetic NOD mice treated with anti-CD3 revert to normoglycemia, the treatment does not permanently abolish the autoimmune lesion in the pancreas; rather, a stable state of insulitis is established, with a demarcation between the inflammatory infiltrate and β-cell mass (39, 40) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the end-point of this lower-dose study was not reached both DEFEND and DEFEND-2 was terminated. The four year follow-up of the patients in the Phase II clinical trial indicated a delayed the rise in insulin requirements of patients (43). Furthermore, in a subgroup of the Phase II trial patients it was shown that recall immunity was preserved adding to the aspect of safety (ref).…”
Section: Ref) the Reader Is Referred To Extensive Reviews Of Animal mentioning
confidence: 98%
“…The Phase II trial with otelixizumab, a humanized non-mitogenic CD3 (ChAgly CD3) monoclonal antibody in newly diagnosed T1D patients suppressed the rise in insulin requirements over 48 months but the effect was related to age and residual c-peptide at diagnosis 43 . The subsequent industry-sponsored Phase III trial (Durable-Response Therapy Evaluation For Early or New-Onset Type 1 Diabetes -DEFEND, NCT00678886) used a cumulated dose of 3 mg as compared to 48 mg for the phase II study.…”
Section: Ref) the Reader Is Referred To Extensive Reviews Of Animal mentioning
confidence: 99%
“…7 At 48 mo the insulin requirements were still better than the placebo group. 42 In addition they stated that a younger age and higher basal β-cell function significantly correlated with improved clinical outcome. 42 However, in the majority of patients receiving Otelixizumab a short-term transient reactivation of the Epstein-Barr virus (EBV) was observed.…”
Section: Ctla4-immunoglobulin Fusion Protein (Abatacept)mentioning
confidence: 99%
“…42 In addition they stated that a younger age and higher basal β-cell function significantly correlated with improved clinical outcome. 42 However, in the majority of patients receiving Otelixizumab a short-term transient reactivation of the Epstein-Barr virus (EBV) was observed. 7,42,43 This self-limited immune response was probably mediated through an activation of EBV-specific T-cells in combination with a short-term general immunosuppression.…”
Section: Ctla4-immunoglobulin Fusion Protein (Abatacept)mentioning
confidence: 99%